A Review on Cryptocurrency and its Advancements in Present World (Journal of Information Technology and Digital World, 2023)
A cryptocurrency is a type of digital or virtual money that may be used to make online purchases of goods and services without requiring actual coins or bills. Cryptocurrency serves as a decentralized means of trade, where each transaction is verified and facilitated via encryption. The blockchain technology that supports cryptocurrency will offer trading transactions in a decentralized nature. The development of IT industry in the recent past has made the idea of cryptocurrencies very popular. Cryptocurrencies are available in a variety of forms, and several businesses use and accept it for transactions. Different types of cryptocurrencies, their benefits, and drawbacks are briefly explained in this study. Additionally, this study discusses about the real-time implementations and upcoming advances.
Keywords: Blockchain; cryptocurrency; peer-to-peer technology; decentralized; hash algorithm